Influence of subinhibitory concentrations of extracts from Psidium cattleianum (Sabine) and Myracrodruon urundeuva (Allemao) on mutans streptococci adhesion to glass and enamel surfaces. - Bianco, Karina Gerhardt; Landucci, Luis Fernando; Schweitzer, Christiane Marie; Gaetti-Jardim, Ellen Cristina; Gaetti-Jardim Júnior, Elerson (ARCHIVES OF HEALTH INVESTIGATION, 2017)
This study evaluated the influence of subinhibitory concentrations of extracts from Myracrodruon urundeuva and Psidium cattleianum on the adhesion of cariogenic cocci to the surface of glass and bovine enamel. The aqueous extracts were prepared from leaves by heating in deionized water and sterilized by filtration (22μm). The minimum inhibitory concentration (MIC) of the extracts on S. mutans ATCC 1910 and ATCC 35688 was determined by the broth dilution method. In the tests of adhesion to glass surfaces, glass tubes were treated with saliva and sucrose and the bacterial strains were cultivated in concentrations equivalent to 25% of MIC, which were also maintained in the adhesion assay. After the contact between the cells and the glass, the unbound cocci were removed and, finally, it was performed the removal of the cells adhered to the glass by sonication. The percentage of adhesion was determined by comparing the number of bacteria adhered to the total inoculated bacteria, in the presence and absence of the subinhibitory concentrations of the extracts. For enamel adhesion tests, bovine enamel samples were standardized, polished, treated with saliva and, in the test group, received the bacterial inoculum and 25% of the MIC of the extracts. The enamel blocks were removed and the total of adhered cocci was determined by cultivation on BHI agar supplemented with horse blood in anaerobic conditions for 48h at 37oC. The results were evaluated through analysis of variance (ANOVA). The extracts were effective in inhibiting bacterial adhesion to glass and dental enamel surfaces, although inhibition varied according to bacterial strain and extract, producing from 40 to 60% of inhibition. The results reinforce the possibility of the use of extracts of plants of the Brazilian savanna in the control of cariogenic biofilms. Descriptors: Bacteria; Prevention & Control; Plant Extracts; Dental Caries.